Experience-based learning during the final year: quantitative content analyses of students’ self-reports - Homberg, Angelika; Narciß, Elisabeth; Thiesbonenkamp-Maag, Julia; Schüttpelz-Brauns, Katrin (Medical teacher, 2023)
The final year offers students the opportunity to explore their future role as a physician in different environments. Learning success depends in large part on how students experience these assignments. The aim of this study is to analyze students’ self-reported experiences to derive factors that promote experience-based learning in the transition phase during the final year of medical school in order to optimally prepare students for professional practice. Data were collected from 2013 to 2019 via written survey after each assignment in the final year. Students were asked to report their pleasant and unpleasant experiences in free-text fields. The text material was analyzed using quantitative content analysis. The authors included 1762 questionnaires for analysis. They formed 12 main categories from the text material, equally covering pleasant and unpleasant experiences. Supervisors and teamwork played a central role in both questions, responsibility and working areas frequently led to positive experiences, and working conditions to negative ones. This study confirms the great importance of supervision. Above all, successful collaboration serves as a door opener into a feeling of security which students need to take on responsibility. The authors adapted Dornan’s model of experience-based learning to the transition phase to help medical schools establish tailored conditions for students’ successful entry into professional practice.